Amelioration of Cd toxicity by pretreatment of salicylic acid in Cicerarietinum L. seedlings - Çanakci, Songül; Dursun, Bahar (Triveni Enterprises, 2013)
In this study, the ameliorating effect of salicylic acid (SA), serving as a mediator for protecting plants, against cadmium (Cd) toxicity in Cicer arietinum was investigated. The seedlings of Cicer arietinum treated with increasing Cd concentrations (0, 25, 50, 100 ?M) inhibited seedling length, reduced fresh and dry weight, total chlorophyll, carotenoid content and fatty acid methyl ester content. Furthermore, the level of some important parameters like MDA, proline and GSH content related to oxidative stress increased in Cd treated seedlings. Leaves of seedlings pretreated with salicylic acid (0.5 mM), alleviated the toxic effects of Cd by increasing the growth parameters, photosynthetic pigments, GSH and FAME content and decreasing proline and MDA content respectively. The result of the present study reveals the protective role of salicylic acid against Cd toxicity in C. arietinum. © Triveni Enterprises, Lucknow (India).
Keywords: Cadmium; Cicer arietinum; Phytotoxicity; Salicylic acid